Effect of Different Methods of Icing on the Quality of Squid and Cuttlefish During Storage - V., Prafulla; Francis, Liju; P.T., Lakshmanan (Fishery Technology, 2025)
Quality changes in squid (Loligo duvauceli) and cuttlefish (Sepia pharaonis), stored under various conditions, viz; (i) direct icing (ii) indirect icing, and (iii) in a mixture of ice and salt at 3% level were evaluated by chemical and sensory methods. The rate of nucleotide degradation was slow for samples kept in the mixture of ice and salt. K-values of samples kept out of direct contact with ice increased at a faster rate than the other two. However, K-values and nucleotide related products showed significant correlation with sensory scores, under these conditions. Total volatile base nitrogen and trimethyl amine nitrogen exhibited a steady and faster rise for indirectly iced samples. There was a significant loss of soluble nitrogenous components and salt in directly iced samples while there was very little loss (<10%) in samples chilled by the other two methods during two weeks period. The study indicated that indirect icing preserves most of the nutrients in squid and cuttlefish, but with shorter shelf life, while chilling in a mixture of salt and ice gave a product of better quality.